A method for preparing ceramic material with high plasticity
By using modified bentonite and maleic anhydride grafted polyethylene wax in ceramic materials, the problem of insufficient plasticity of ceramic materials is solved, and the preparation of high plasticity of ceramic materials is achieved.
Patent Information
- Application Number
- CN202410773978.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-17
AI Technical Summary
The plasticity of existing ceramic materials is poor and it is difficult to meet certain application needs.
A highly plastic ceramic material is formed by stirring and mixing yellow clay, porcelain stone, modified bentonite and maleic anhydride grafted polyethylene wax at specific ratios and temperatures. Modified bentonite increases its interface compatibility and mechanical properties through acidification and hydroxylation treatment.
It significantly improves the plasticity of ceramic materials, allowing them to better deform and adapt to different shapes when subjected to external forces, and is suitable for a variety of application scenarios.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, in particular to a method for preparing a ceramic material with high plasticity. Background Art
[0002] Ceramics is a general term for pottery and porcelain. Pottery is made of clay with high viscosity and strong plasticity as the main raw material. It is opaque, has fine pores and weak water absorption. Porcelain is made of clay, feldspar and quartz. Modern ceramics are also called new ceramics, fine ceramics or special ceramics, but have poor plasticity. How to improve the plasticity of ceramics is the key to solving the problem.
[0003] Bentonite is mainly used in clay gravel. It has high plasticity and strong adhesion. When used in ceramics, it helps to deform when subjected to external forces. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a ceramic material with high plasticity, which has good plasticity.
[0006] (II) Technical solution
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for preparing a ceramic material with high plasticity, the method for preparing a ceramic material with high plasticity comprising the following steps: adding 40-60 parts by weight of yellow clay, 20-40 parts by weight of porcelain stone, 10-30 parts by weight of modified bentonite, and 5-15 parts by weight of maleic anhydride grafted polyethylene wax into a stirrer, stirring and mixing at 80-120°C for 3-6h to obtain a mixture, and then pouring the mixture into a ceramic blank, cooling, and obtaining a ceramic material with high plasticity.
[0008] Preferably, the preparation method of the modified bentonite comprises the following steps:
[0009] (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing the mixture in ethanol, adding KH560 and stirring for reaction, filtering, washing and drying to obtain epoxy bentonite;
[0010] (2) Adding the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid tetrahydrofuran solution, and propylene alcohol to the methanol solvent, stirring evenly, adding silicone rubber, ultrasonically dispersing evenly, reacting at 50-80° C. for 3-5 hours, cooling, centrifuging, washing, and drying to obtain hydroxylated silicone rubber
[0011] (3) Adding Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stirring and mixing, and then continuing to add dibutyltin dilaurate catalyst, reacting at 60-90° C. for 6-12 hours, and then adding trifluoroacetic acid for deprotection, and after completion, distilling under reduced pressure, filtering and drying to obtain amino silicone rubber;
[0012] (4) mixing phenolic resin and epichlorohydrin uniformly, reacting at 75-95° C. for 6-12 hours, and then concentrating under reduced pressure and washing to obtain epoxidized phenolic resin;
[0013] (5) Add epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, heat in a water bath at 70-90° C. for 6-10 h, wash with anhydrous ethanol after the reaction, and dry to obtain modified bentonite.
[0014] Preferably, the mass ratio of bentonite to KH560 in (1) is 1:1.2-1.5.
[0015] Preferably, in (2), the mass ratio of the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid, the acryl alcohol, and the silicone rubber is 0.01-0.03:0.02-0.03:1.2-1.4:1.2-1.6.
[0016] Preferably, the mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid in (3) is 1:0.8-1.3:1.2-1.5:0.2-0.3:0.2-0.4.
[0017] Preferably, the mass ratio of phenolic resin to epichlorohydrin in (4) is 1:1.3-1.6.
[0018] Preferably, the mass ratio of the epoxidized phenolic resin to the amino silicone rubber in (5) is 1.1-1.3:1.2-1.5.
[0019] (III) Beneficial technical effects
[0020] The invention provides a ceramic material with high plasticity by adding yellow clay, porcelain stone, modified bentonite and maleic anhydride grafted polyethylene wax into a stirrer, stirring and mixing to obtain a mixture, then pouring the mixture into a ceramic blank, cooling and obtaining the ceramic material.
[0021] During the melt blending process, the anhydride groups in the maleic anhydride grafted polyethylene wax will undergo a ring-opening reaction with the hydroxyl groups in the modified bentonite, so that the bentonite and polyethylene wax have good interfacial compatibility and mechanical properties. The bentonite is grafted on the phenolic resin to form organic-inorganic hybrid particles, which can be evenly distributed in the ceramic material; the silicone rubber in the modified bentonite has good elasticity and resilience, and high plasticity, and is used in ceramics to further improve the plasticity of ceramic materials; the phenolic resin not only has good heat resistance, but also can still maintain high physical properties and chemical stability at high temperatures. The phenolic resin has high hardness and elasticity, so it will synergize with silicone rubber when used in ceramics to improve the plasticity of the ceramic. DETAILED DESCRIPTION
[0022] Example 1
[0023] (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing the mixture in ethanol, adding KH560 and stirring the mixture for reaction, wherein the mass ratio of bentonite to KH560 is 1:1.2, filtering, washing and drying to obtain epoxy bentonite;
[0024] (2) adding a polymerization inhibitor, butylated hydroxytoluene, a tetrahydrofuran solution of chloroplatinic acid, and propylene alcohol to a methanol solvent, stirring evenly, adding silicone rubber, wherein the mass ratio of the polymerization inhibitor, butylated hydroxytoluene, the catalyst, chloroplatinic acid, propylene alcohol, and silicone rubber is 0.01:0.02:1.2:1.2, ultrasonically dispersing evenly, reacting at 50° C. for 3 h, cooling, centrifuging, washing, and drying to obtain hydroxylated silicone rubber;
[0025] (3) Add Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stir and mix, then continue to add dibutyltin dilaurate catalyst, react at 60° C. for 6 hours, and then add trifluoroacetic acid for deprotection, wherein the mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid is 1:0.8:1.2:0.2:0.2, and after completion, distill under reduced pressure, filter and dry to obtain amino silicone rubber;
[0026] (4) mixing phenolic resin and epichlorohydrin uniformly, wherein the mass ratio of phenolic resin to epichlorohydrin is 1:1.3, reacting at 75° C. for 6 hours, and then concentrating under reduced pressure and washing to obtain epoxidized phenolic resin;
[0027] (5) adding epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, wherein the mass ratio of epoxidized phenolic resin to amino silicone rubber is 1.1:1.2, heating in a water bath at 70° C. for 6 h, washing with anhydrous ethanol after the reaction, and drying to obtain modified bentonite;
[0028] (6) 40 parts by weight of yellow clay, 20 parts by weight of porcelain stone, 10 parts by weight of modified bentonite, and 5 parts by weight of maleic anhydride grafted polyethylene wax are added into a stirrer, and stirred and mixed at 80° C. for 3 hours to obtain a mixture, and then the mixture is poured into a ceramic blank and cooled to obtain a ceramic material with high plasticity.
[0029] Example 2
[0030] (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing the mixture in ethanol, adding KH560 and stirring the mixture for reaction, wherein the mass ratio of bentonite to KH560 is 1:1.5, filtering, washing and drying to obtain epoxy bentonite;
[0031] (2) adding a polymerization inhibitor, butylated hydroxytoluene, a tetrahydrofuran solution of chloroplatinic acid, and propylene alcohol to a methanol solvent, stirring evenly, adding silicone rubber, wherein the mass ratio of the polymerization inhibitor, butylated hydroxytoluene, the catalyst, chloroplatinic acid, propylene alcohol, and silicone rubber is 0.03:0.03:1.4:1.6, ultrasonically dispersing evenly, reacting at 80° C. for 5 h, cooling, centrifuging, washing, and drying to obtain hydroxylated silicone rubber;
[0032] (3) Add Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stir and mix, then continue to add dibutyltin dilaurate catalyst, react at 90° C. for 12 hours, and then add trifluoroacetic acid for deprotection, wherein the mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid is 1:1.3:1.5:0.3:0.4, and after completion, distill under reduced pressure, filter and dry to obtain amino silicone rubber;
[0033] (4) mixing phenolic resin and epichlorohydrin uniformly, wherein the mass ratio of phenolic resin to epichlorohydrin is 1:1.6, reacting at 95° C. for 12 h, and then concentrating under reduced pressure and washing to obtain epoxidized phenolic resin;
[0034] (5) adding epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, wherein the mass ratio of epoxidized phenolic resin to amino silicone rubber is 1.3:1.5, heating in a water bath at 90° C. for 10 h, washing with anhydrous ethanol after the reaction, and drying to obtain modified bentonite;
[0035] (6) Add 60 parts by weight of yellow clay, 40 parts by weight of porcelain stone, 30 parts by weight of modified bentonite, and 15 parts by weight of maleic anhydride grafted polyethylene wax into a stirrer, stir and mix at 120° C. for 6 hours to obtain a mixture, then pour the mixture into a ceramic blank, cool it, and obtain a ceramic material with high plasticity.
[0036] Example 3
[0037] (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing the mixture in ethanol, adding KH560 and stirring the mixture for reaction, wherein the mass ratio of bentonite to KH560 is 1:1.35, filtering, washing and drying to obtain epoxy bentonite;
[0038] (2) adding a polymerization inhibitor, butylated hydroxytoluene, a tetrahydrofuran solution of chloroplatinic acid, and propylene alcohol to a methanol solvent, stirring evenly, adding silicone rubber, wherein the mass ratio of the polymerization inhibitor, butylated hydroxytoluene, the catalyst, chloroplatinic acid, propylene alcohol, and silicone rubber is 0.02:0.025:1.3:1.4, ultrasonically dispersing evenly, reacting at 65° C. for 4 hours, cooling, centrifuging, washing, and drying to obtain hydroxylated silicone rubber;
[0039] (3) Add Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stir and mix, then continue to add dibutyltin dilaurate catalyst, react at 75° C. for 9 hours, and then add trifluoroacetic acid for deprotection, wherein the mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid is 1:1.05:1.35:0.25:0.3, and after completion, distill under reduced pressure, filter and dry to obtain amino silicone rubber;
[0040] (4) mixing phenolic resin and epichlorohydrin uniformly, wherein the mass ratio of phenolic resin to epichlorohydrin is 1:1.45, reacting at 85° C. for 9 hours, and then concentrating under reduced pressure and washing to obtain epoxidized phenolic resin;
[0041] (5) adding epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, wherein the mass ratio of epoxidized phenolic resin to amino silicone rubber is 1.2:1.35, heating in a water bath at 80° C. for 8 h, washing with anhydrous ethanol after the reaction, and drying to obtain modified bentonite;
[0042] (6) Add 50 parts by weight of yellow clay, 30 parts by weight of porcelain stone, 20 parts by weight of modified bentonite, and 10 parts by weight of maleic anhydride grafted polyethylene wax into a stirrer, stir and mix at 100° C. for 4.5 hours to obtain a mixture, then pour the mixture into a ceramic blank, cool it, and obtain a ceramic material with high plasticity.
[0043] Example 4
[0044] (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing the mixture in ethanol, adding KH560 and stirring the mixture for reaction, wherein the mass ratio of bentonite to KH560 is 1:1.2, filtering, washing and drying to obtain epoxy bentonite;
[0045] (2) adding a polymerization inhibitor, butylated hydroxytoluene, a tetrahydrofuran solution of chloroplatinic acid, and propylene alcohol to a methanol solvent, stirring evenly, adding silicone rubber, wherein the mass ratio of the polymerization inhibitor, butylated hydroxytoluene, the catalyst, chloroplatinic acid, propylene alcohol, and silicone rubber is 0.01:0.02:1.2:1.2, ultrasonically dispersing evenly, reacting at 50° C. for 3 h, cooling, centrifuging, washing, and drying to obtain hydroxylated silicone rubber;
[0046] (3) Add Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stir and mix, then continue to add dibutyltin dilaurate catalyst, react at 90° C. for 12 hours, and then add trifluoroacetic acid for deprotection, wherein the mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid is 1:1.3:1.5:0.3:0.4, and after completion, distill under reduced pressure, filter and dry to obtain amino silicone rubber;
[0047] (4) mixing phenolic resin and epichlorohydrin uniformly, wherein the mass ratio of phenolic resin to epichlorohydrin is 1:1.6, reacting at 95° C. for 12 h, and then concentrating under reduced pressure and washing to obtain epoxidized phenolic resin;
[0048] (5) adding epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, wherein the mass ratio of epoxidized phenolic resin to amino silicone rubber is 1.2:1.35, heating in a water bath at 80° C. for 8 h, washing with anhydrous ethanol after the reaction, and drying to obtain modified bentonite;
[0049] (6) Add 50 parts by weight of yellow clay, 30 parts by weight of porcelain stone, 20 parts by weight of modified bentonite, and 10 parts by weight of maleic anhydride grafted polyethylene wax into a stirrer, stir and mix at 100° C. for 4.5 hours to obtain a mixture, then pour the mixture into a ceramic blank, cool it, and obtain a ceramic material with high plasticity.
[0050] Example 5
[0051] (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing the mixture in ethanol, adding KH560 and stirring the mixture for reaction, wherein the mass ratio of bentonite to KH560 is 1:1.5, filtering, washing and drying to obtain epoxy bentonite;
[0052] (2) adding a polymerization inhibitor, butylated hydroxytoluene, a tetrahydrofuran solution of chloroplatinic acid, and propylene alcohol to a methanol solvent, stirring evenly, adding silicone rubber, wherein the mass ratio of the polymerization inhibitor, butylated hydroxytoluene, the catalyst, chloroplatinic acid, propylene alcohol, and silicone rubber is 0.03:0.03:1.4:1.6, ultrasonically dispersing evenly, reacting at 80° C. for 5 h, cooling, centrifuging, washing, and drying to obtain hydroxylated silicone rubber;
[0053] (3) Add Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stir and mix, then continue to add dibutyltin dilaurate catalyst, react at 75° C. for 9 hours, and then add trifluoroacetic acid for deprotection, wherein the mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid is 1:1.05:1.35:0.25:0.3, and after completion, distill under reduced pressure, filter and dry to obtain amino silicone rubber;
[0054] (4) mixing phenolic resin and epichlorohydrin uniformly, wherein the mass ratio of phenolic resin to epichlorohydrin is 1:1.45, reacting at 85° C. for 9 hours, and then concentrating under reduced pressure and washing to obtain epoxidized phenolic resin;
[0055] (5) adding epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, wherein the mass ratio of epoxidized phenolic resin to amino silicone rubber is 1.1:1.2, heating in a water bath at 70° C. for 6 h, washing with anhydrous ethanol after the reaction, and drying to obtain modified bentonite;
[0056] (6) 40 parts by weight of yellow clay, 20 parts by weight of porcelain stone, 10 parts by weight of modified bentonite, and 5 parts by weight of maleic anhydride grafted polyethylene wax are added into a stirrer, and stirred and mixed at 80° C. for 3 hours to obtain a mixture, and then the mixture is poured into a ceramic blank and cooled to obtain a ceramic material with high plasticity.
[0057] Comparative Example 1
[0058] 40 parts by weight of yellow clay and 20 parts by weight of porcelain stone are added into a stirrer, and the mixture is stirred and mixed at 80° C. for 3 hours to obtain a mixture, and then the mixture is poured into a ceramic blank and cooled to obtain a ceramic material with high plasticity.
[0059] The ceramics with high plasticity obtained in the embodiments and comparative examples were subjected to plasticity experiments. The plasticity R of the mud cake was measured by the plasticity index method using a KS-B microcomputer plasticity tester. The test results are shown in Table 1.
[0060] Table 1: Plasticity tests.
[0061] project Plasticity R Example 1 0.745 Example 2 0.768 Example 3 0.764 Example 4 0.734 Example 5 0.786 Comparative Example 1 0.651
[0062] It can be seen from Table 1 that the ceramic material of the present invention has high plasticity.
[0063] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a ceramic material with high plasticity, characterized in that: The preparation method of the ceramic material with high plasticity comprises the following steps: adding 40-60 parts by weight of yellow clay, 20-40 parts by weight of porcelain stone, 10-30 parts by weight of modified bentonite, and 5-15 parts by weight of maleic anhydride grafted polyethylene wax into a stirrer, stirring and mixing at 80-120° C. for 3-6 hours to obtain a mixture, and then pouring the mixture into a ceramic blank, cooling, and obtaining a ceramic material with high plasticity; The preparation method of the modified bentonite comprises the following steps: (1) adding bentonite to a hydrochloric acid solution for acidification to obtain acid-modified bentonite and dispersing it in ethanol, adding KH560 and stirring to react, filtering, washing and drying to obtain epoxy bentonite; (2) Adding the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid tetrahydrofuran solution, and propylene alcohol to the methanol solvent and stirring evenly, adding the silicone rubber, ultrasonically dispersing evenly, reacting at 50-80°C for 3-5h, cooling, centrifuging, washing and drying to obtain the hydroxylated silicone rubber; (3) Add Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, and hydroxylated silicone rubber to N,N-dimethylformamide solvent, stir and mix, then continue to add dibutyltin dilaurate catalyst, react at 60-90°C for 6-12h, then add trifluoroacetic acid for deprotection, and after completion, perform vacuum distillation, filter and dry to obtain amino silicone rubber; (4) Mix the phenolic resin and epichlorohydrin evenly, react at 75-95°C for 6-12 hours, then concentrate under reduced pressure and wash to obtain an epoxidized phenolic resin; (5) Add epoxidized phenolic resin and amino silicone rubber to N,N-dimethylformamide solvent, heat in a water bath at 70-90°C for 6-10 hours, wash with anhydrous ethanol after the reaction, and dry to obtain modified bentonite.
2. The method for preparing a ceramic material with high plasticity according to claim 1, characterized in that: The mass ratio of bentonite to KH560 in (1) is 1:1.2-1.
5.
3. The method for preparing a ceramic material with high plasticity according to claim 1, characterized in that: The mass ratio of the polymerization inhibitor dibutyl hydroxytoluene, the catalyst chloroplatinic acid, the propenyl alcohol and the silicone rubber in (2) is 0.01-0.03:0.02-0.03:1.2-1.4:1.2-1.
6.
4. The method for preparing a ceramic material with high plasticity according to claim 1, characterized in that: The mass ratio of Boc-4-aminomethyl-1,1-cyclohexanedicarboxylic acid, epoxy bentonite, hydroxylated silicone rubber, dibutyltin dilaurate catalyst, and trifluoroacetic acid in (3) is 1:0.8-1.3:1.2-1.5:0.2-0.3:0.2-0.
4.
5. The method for preparing a ceramic material with high plasticity according to claim 1, characterized in that: The mass ratio of phenolic resin to epichlorohydrin in (4) is 1:1.3-1.
6.
6. The method for preparing a ceramic material with high plasticity according to claim 1, characterized in that: The mass ratio of the epoxidized phenolic resin to the amino silicone rubber in (5) is 1.1-1.3:1.2-1.5.
Citation Information
Patent Citations
Illuminant ceramic mud composition for mud extruding process and preparation method thereof
CN107473707A
Environment-friendly ceramic with high breathability
CN108840661A